Tantangan Perusahaan di Indonesia dalam Menghadapi Persaingan Global - Mulyani, Ninuk (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2002)
Indonesian companies are at present encountering great challenges in this global competition, because most of them still focus on their domestic market and are not aware of global competitors who are able to produce goods with better quality and lower price, Moreover the implementation of AFTA starting January 1, 2002 has made Indonesian and other ASEAN products enter ASEAN market more easily. For this reason, Indonesian companies should do their best lo improve the quality of their products and to create competitive advantages lo compete with the products from other countries.